2022
DOI: 10.3389/fpsyt.2021.788898
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Depression, Anxiety, and Stress During the Second Wave of COVID-19 in Slovenia

Abstract: The spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) pandemic has led to numerous negative consequences on the mental health of the population throughout the world. The main aim of our study was to compare the risk for depression, anxiety, and stress during the second wave of the pandemic in Slovenia. An additional goal was to analyze the association of depression, anxiety, and stress, with the most relevant subjective factors that define the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
5
10
0
Order By: Relevance
“…Notwithstanding the adoption of this regional approach consisting of lighter restraining measures than the first lockdown, some longitudinal investigations showed a persistent impact of the emergency period on sleep (Conte et al, 2021 ; Salfi et al, 2021a ) and mental health (Salfi et al, 2021a ) among the Italian population during the second contagion wave. These results were consistent with the international literature confirming long‐lasting repercussions on sleep features (Basishvili et al, 2021 ; Liu et al, 2022 ; Trakada et al, 2022 ) and psychological measures (Benke et al, 2022 ; Chodkiewicz et al, 2021 ; Daly & Robinson, 2022 ; Rus Prelog et al, 2022 ; Wetherall et al, 2022 ) during the second COVID‐19 wave, suggesting the urgency of large‐scale interventions to preserve the general well‐being. In the last days of 2020, the administration of the first COVID‐19 vaccine to the adult population was authorised by the European and Italian medicines agencies.…”
Section: Introductionsupporting
confidence: 91%
“…Notwithstanding the adoption of this regional approach consisting of lighter restraining measures than the first lockdown, some longitudinal investigations showed a persistent impact of the emergency period on sleep (Conte et al, 2021 ; Salfi et al, 2021a ) and mental health (Salfi et al, 2021a ) among the Italian population during the second contagion wave. These results were consistent with the international literature confirming long‐lasting repercussions on sleep features (Basishvili et al, 2021 ; Liu et al, 2022 ; Trakada et al, 2022 ) and psychological measures (Benke et al, 2022 ; Chodkiewicz et al, 2021 ; Daly & Robinson, 2022 ; Rus Prelog et al, 2022 ; Wetherall et al, 2022 ) during the second COVID‐19 wave, suggesting the urgency of large‐scale interventions to preserve the general well‐being. In the last days of 2020, the administration of the first COVID‐19 vaccine to the adult population was authorised by the European and Italian medicines agencies.…”
Section: Introductionsupporting
confidence: 91%
“…Notwithstanding the adoption of this regional approach consisting of lighter restraining measures than the first lockdown, some longitudinal investigations showed a persistent impact of the emergency period on sleep (Conte et al, 2021; and mental health among the Italian population during the second contagion wave. These results were consistent with the international literature confirming long-lasting repercussions on sleep features (Basishvili et al, 2021;Liu et al, 2022;Trakada et al, 2022) and psychological measures (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) during the second COVID-19 wave, suggesting the urgency of large-scale interventions to preserve the general well-being. In the last days of 2020, the administration of the first COVID-19 vaccine to the adult population was authorised by the European and Italian medicines agencies.…”
Section: Introductionsupporting
confidence: 91%
“…Specifically, younger people (Amicucci et al, 2021;Daly et al, 2020;Jahrami et al, 2022;Rossi et al, 2020) and women (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021) reported higher rates of sleep disturbances and psychological symptoms. These results were confirmed by Italian and European studies (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) addressing the effect of the second wave of COVID-19. Similarly, the evening chronotype was associated with more evident changes in sleep patterns and increased sleep and mental health problems both during the lockdown (Bottary et al, 2022;Merikanto et al, 2022;Salfi, Lauriola, et al, 2021) and the second contagion wave .…”
Section: Introductionsupporting
confidence: 68%
“…In contrast, despite all the challenges that the older population may face during the pandemic, lower rates of mental distress in this population compared to younger age groups have been reported, with older adults faring better than younger adults in multiple metrics of mental health ( 33 ). Several large representative surveys of adults in the US ( 34 ), UK ( 35 ), Denmark ( 36 ), Slovenia ( 37 ) and China ( 38 ) have also found an inverse relationship between age and mental health symptoms. Compared to younger adults, older adults seem to respond to the pandemic with a more positive emotional response and reported lower rates of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Such inconsistencies emphasize the need for further research to explore age differences in the psychological impact of COVID-19, whilst taking into consideration of the potential confounding effects of various social determinants of mental health changes during the COVID-19 pandemic such as female, lower socioeconomic status as well as subjective poorer physical health ( 42 44 ). Moreover, it is worth noting that most of the studies outlined above (except Pedersen et al ( 36 ) and Prelog et al ( 37 )) provided only a snapshot of the immediate and the early months of the mental health responses following the COVID-19 outbreak, which may evolve with the development of the pandemic, public health interventions, and repeated exposure to social distancing regulations.…”
Section: Introductionmentioning
confidence: 99%